THE ANALYSIS ON THE DEVELOPMENT OF THE KABELA AS A SYMBOL OF TRADITIONAL HONOUR FOR THE PEOPLE OF BOLAANG MONGONDOW - Sumardiko; Kolibu, Ronald M. P.; Pangkey, Ferdinand (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
This research aims to explain the development of Kabela in Bolaang Mongondow culture and its philosophical meaning. Kabela is a container for placing betel (obuyu'), areca nut (mama'an), whiting and tobacco (tabaku') as a banquet for guests. The type of research used in this study is qualitative using a descriptive approach. Data collection techniques through observation, interviews, and documentation. Data sources in this study are divided into two, namely primary data from interviews and secondary data from written records. Data analysis in this study uses data reduction, data review and conclusion drawing. The results of this study show that there are several developments in the form of Kabela from simple forms to having decorations. There are past motifs such as pata' lumandai, pata' malasai, and current motifs such as coconut, flower and geometric motifs. The colours used in the past were red, white and black while today additional colours such as green, yellow, blue, purple and others are used. Each creation of Kabela used to have various philosophical meanings while the current Kabela emphasises more on aesthetic value. It is hoped that the community, especially Bolaang Mongondow, can continue to preserve this historical art object so that it is not lost or forgotten by future generations.